2011
DOI: 10.3846/mla.2011.097
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Iron Salt on Anaerobic Digestion and Phosphate Release to Sludge Liquor / Geležies Druskos Įtaka Anaerobinio Dumblo Pūdymo Procesui Ir Fosfatų Išsiskyrimui Į Dumblo Vandenį

Abstract: Iron salts are used at wastewater treatment plants (WWTPs) for several reasons: for removing chemical phosphorus, preventing from struvite formation and reducing the content of hydrogen sulfide (H2S) in biogas. Anaerobic digestion is a common scheme for sludge treatment due to producing biogas that could be used as biofuel. Laboratory analysis has been carried out using anaerobic digestion model W8 (Armfield Ltd, UK) to investigate any possible effect of adding FeCl3 on the anaerobic digestion of primary sludg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…Pasak S. Ofverstrom (2014), geležies chloridas yra plačiai naudojama druska, kuri sumažina vandenilio sulfido koncentraciją biodujose ir struvito susidarymą, bet sumažina fosfatų šalinimą pūdant dumblą anaerobiniu būdu. Taip pat S. Ofverstrom, R. Dauknio ir I. Sapkaitės (2011) teigimu, įterpus geležies chloridą į dumblo pūdymo procesą biodujų išeiga sumažėja vidutiniškai 30 %.…”
Section: įVadasunclassified
“…Pasak S. Ofverstrom (2014), geležies chloridas yra plačiai naudojama druska, kuri sumažina vandenilio sulfido koncentraciją biodujose ir struvito susidarymą, bet sumažina fosfatų šalinimą pūdant dumblą anaerobiniu būdu. Taip pat S. Ofverstrom, R. Dauknio ir I. Sapkaitės (2011) teigimu, įterpus geležies chloridą į dumblo pūdymo procesą biodujų išeiga sumažėja vidutiniškai 30 %.…”
Section: įVadasunclassified
“…P effluent limits are predicted to become stricter in the future, especially in vulnerable areas such as the Baltic Sea [27], thus increasing the need to implement CPR because it is relatively difficult to reach low P effluent concentrations with EBPR. Furthermore, many papers discuss the effect of adding metal coagulants to digesters treating sludge from an EBPR process to prevent P release [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Iron(III) compounds, such as Fe(OH) 2 , Fe r PO 4 (OH) 3r-3 , and FePO 4 , are reduced to iron(II) in anaerobic digestion (AD) [35]. The presence of iron(II) in digestate decreases the soluble phosphate [28,29], as Fe(II) precipitates as different species. Mamais et al [36] suggested that Fe 3 (PO 4 ) 2 leads to a low soluble PO 4 3− concentration, but Korving et al [13] concluded that the chemistry of iron is not entirely understood.…”
Section: Introductionmentioning
confidence: 99%